Stability analysis model of Plasmodium vivax from Anopheles in human infection using SIDR population compartment with treatment RTS-S/AS01 vaccine in Yogyakarta - - Prihantini, Pratama Yoga Bagas, Muhammad Ammar, (Universiti Pendidikan Sultan Idris, 2017)
Stability analysis model of Plasmodium vivax from Anopheles in human infection using SIDR population compartment with treatment RTS-S/AS01 vaccine in Yogyakarta by - Prihantini, Pratama Yoga Bagas, Muhammad Ammar,